(untitled) (Global Journal of Science Frontier Research, 2015)
Prevalence of intestinal helminth infections in primary schools in Isuochi town, Abia State Nigeria was surveyed in two randomly selected primary schools, between April and September 2012. Stool samples of 200 pupils (110 males, 90 females), aged 6-9 years, were examined microscopically by using wet mount (normal saline) and concentrated saturated sodium chloride floatation techniques. Seven intestinal helminths, AscarisIumbricoides, Hookworm, Trichuristri-chiura, Strongyloidesstercoralis, Enterobiusvermicularis, Schistosomamansoni and Taeniaspp, were identified with 150(75%) of the 200 pupils infected with one or a combination of the worms. Hookworm had the highest prevalence (37.84%) followed by A. lumbricoides (24.32%), T. trichiura(14.86%), E. vermicularis(8.11%), S. stercoralis and T. spp have (6.76%) infection rate respectively while S. mansonihas the lowest rate of infection (2.70%).